Effects of 17β-estradiol and equilin on atherosclerosis development in female Apoe shl mice - Akiyo Kakibuchi; Fumitake Ito; Osamu Takaoka; Nanami Tahara; Mari Kawamata; Kazuya Yabumoto; Akihisa Katayama; Yuko Izumi; Eiko Maeda; Taisuke Mori (Scientific Reports)
Abstract The effects of conjugated equine estrogens (CEE) and 17β-estradiol-based hormone replacement therapy (HRT) on atherosclerosis development remain controversial. Here, we investigated the effects of equilin, a major compound in CEE, and 17β-estradiol on atherosclerosis development in an atherosclerotic mouse model. Female B6.KOR/StmSlc-Apoe shl mice were ovariectomized and fed a high-fat diet for 9 and 12 weeks (early and late groups, respectively) and then treated with 17β-estradiol or equilin. Atherosclerotic lesions in the aortic arch and brachiocephalic artery (BCA) were assessed at the end of the experimental period. Compared with placebo, equilin and 17β-estradiol significantly inhibited atherosclerotic lesion formation in the aortic arch and BCA in both groups. However, 17β-estradiol had a significantly greater inhibitory effect than equilin in the late group. Although 17β-estradiol significantly inhibited atherosclerosis progression in the aortic root, no significant difference was observed between the equilin and placebo groups. Additionally, compared with equilin, 17β-estradiol significantly inhibited atherosclerotic plaque formation in the aortic root. Moreover, 17β-estradiol exerted a stronger inhibitory effect on atherogenesis than equilin and control. Both 17β-estradiol and equilin protect against atherosclerotic plaque formation in the vascular endothelium, with 17β-estradiol exhibiting a superior effect.